Efficiency, Performance, Potential Improvement and Dual Banking Analysis of BPR & BPRS in West Java, Indonesia - Aufa; Mimma; Syahdatul Maulida (Review on Islamic Accounting, 2022)
SMEs are crucial to reviving the national economy in times of economic globalization and the Covid-19 pandemic. One of the tactics required to boost the competitiveness of MSMEs is to take use of efficient financing options offered by banks. This study compares the effectiveness, effectiveness, and improvement potential of BPR and BPRS in West Java and their applicability to MSMEs. Data Envelopment Analysis (DEA) is the analysis employed, and the study period is from 2016 to 2021. The banking sector in Indonesia includes BPR and BPRS. In order to successfully navigate the era of economic globalization and national economic recovery, it is critical to assess the degree to which these two banks can collaborate in the best possible way to promote increased prosperity and competitiveness of MSMEs, primarily through productive financing. In West Java, 20 BPRs and 20 BPRS served as the research samples. The information used is secondary information gleaned from each bank's annual financial reports for the years 2016 through 2021. The study's input variables are third-party money, operating costs, and fixed assets. Operating income and provided funding are additional output variables. The findings of this study demonstrate that efficiency trends for BPR and BPRS in West Java varied across the study period of 2016–2021. While BPRS saw a considerable reduction throughout the epidemic, West Java's BPR efficiency remained constant. Furthermore, in West Java, BPRs are more efficient than BPRS when comparing the two types of banks. This study also examines potential changes that could be made to programs to reduce input and output-related inefficiencies. Furthermore, the output variables, notably the financing variables offered, are generally the root of the two types of banks' most important inefficiencies. Additionally, this study makes recommendations to academics, practitioners, and regulators.